2012
DOI: 10.1248/bpb.b12-00028
|View full text |Cite
|
Sign up to set email alerts
|

Interferon Gamma Induces Steroid Sulfatase Expression in Human Keratinocytes

Abstract: Key words steroid sulfatase; keratinocyte; interferon gamma; nuclear factor-kappa B; dexamethasone Steroid sulfatase (STS) is a microsomal enzyme that catalyzes the hydrolysis of sulfated 3-hydroxysteroids to the corresponding free active 3-hydroxysteroids.1) This enzyme is widely distributed throughout the body, and its actions are implicated in both physiological processes and pathological conditions. In many peripheral organs such as skin STS play a key role in the production of dehydroepiandrosterone (DHEA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…It is located proximal to the portion of the gene that encodes enzyme expression, but the promoter sequence varies in a tissue-specific fashion [54]. While cytokines such as TNFα and IL-6 upregulate enzyme activity, IL-1β instead reportedly downregulates SSase activity [55], although IL-1β (as well as interferon γ) reportedly down-regulate SSase expression by inhibiting NFkB, while activating the glucocorticoidreceptor [55]. Finally, both retinoids and 1,25(OH) 2 vitamin D3 induce both SSase activity and expression [56].…”
Section: Molecular Biology and Regulation Of Ssasementioning
confidence: 99%
“…It is located proximal to the portion of the gene that encodes enzyme expression, but the promoter sequence varies in a tissue-specific fashion [54]. While cytokines such as TNFα and IL-6 upregulate enzyme activity, IL-1β instead reportedly downregulates SSase activity [55], although IL-1β (as well as interferon γ) reportedly down-regulate SSase expression by inhibiting NFkB, while activating the glucocorticoidreceptor [55]. Finally, both retinoids and 1,25(OH) 2 vitamin D3 induce both SSase activity and expression [56].…”
Section: Molecular Biology and Regulation Of Ssasementioning
confidence: 99%
“…These properties, as well as the relative long life of a keratinocyte compared with other inflammatory cells such as the neutrophil or eosinophil, make the keratinocyte a potentially important player in the amplification and persistence of inflammatory and immune responses in AD. Several groups have reported that GC exhibits anti-inflammatory eff ;ects in keratinocytes treated with TNFα [32,33], hapten [34], UV-B irradiation [35], IFNg [36], and induces keratinocyte terminal differentiation [37]. However, few investigations have been conducted to determine whether SEB contributes to the resistance to GCs through keratinocytes.…”
Section: Discussionmentioning
confidence: 99%
“…G6PD E:S then acts as a sink for DHEA, stimulating OATP2B1, the transport protein responsible for importing DHEAS into the cell. Inactivation of TP53 also hyperactivates NFKB ( Weisz et al 2007 , Kawauchi et al 2008 , Cooks et al 2013 ), triggering steroid sulfatase ( Hattori et al 2012 , Dias & Selcer 2016 ), which potentiates the importation of DHEAS and its intracellular activation to DHEA. OATP2B1 is also stimulated by the intracellular presence of de-sulfated androgens ( Grube et al 2006 ), such that as the intracellular concentration of DHEA rises, DHEAS is imported into the p53-affected cell at an ever-accelerating rate.…”
Section: Introductionmentioning
confidence: 99%